Cryptography and network security : principles and practices - Stallings, William (Pearson/Prentice Hall, 2006)
In this age of viruses and hackers, of electronic eavesdropping and electronic fraud, security is paramount. This solid, up-to-date tutorial is a comprehensive treatment of cryptography and network security is ideal for self-study. Explores the basic issues to be addressed by a network security capability through a tutorial and survey of cryptography and network security technology. Examines the practice of network security via practical applications that have been implemented and are in use today. Provides a simplified AES (Advanced Encryption Standard) that enables readers to grasp the essentials of AES more easily. Features block cipher modes of operation, including the CMAC mode for authentication and the CCM mode for authenticated encryption. Includes an expanded, updated treatment of intruders and malicious software. A useful reference for system engineers, programmers, system managers, network managers, product marketing personnel, and system support specialists.